MONOCULAR TEMPORAL HEMIANOPIA: IN REPEATED ISCHEMIC STROKE ATTACKS - Ari Bandana Tasrif; Nona Suci Rahayu (PT. Radja Intercontinental Publishing, 2025)
Hemianopsia is a visual impairment characterized by the loss of half of the visual field in one or both eyes. This condition can be temporary or permanent. Monocular temporal hemianopia is one of them, namely visual field abnormalities in one eye in the temporal part, this abnormality is located in the occipital and temporal cortex. Disorders in this area can be caused by ischemic conditions. This case is rarely reported. This article presents a case study of a 56-year-old male patient with a history of chronic hypertension who came to the emergency unit with sudden loss of visual field on the right side of the eye, the patient had a history of ischemic stroke 1 year ago and did not leave any residual symptoms. Initial examination showed blood pressure of 190/110 mmHg accompanied by severe headache. CT scan showed recurrent ischemia in the left occipital and temporal lobes. The main focus of initial treatment is to restore cerebral blood flow through the administration of neuroprotective agents and antiplatelet therapy, which aims to optimize cerebral perfusion.